Livestock in Central Asia: From rural subsistence to engine of growth? - Sarah Robinson (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2020)
This paper presents an overview of the livestock sector in Central Asia using national statistics and field survey data. Growing consumer demand and underused pasture reserves suggest significant potential for growth. But production is fragmented between many small household producers with poor access to land, family farms and very large (but often inefficient) enterprises. Few producers can supply quality livestock products at high volumes, leading some meat and milk processors to favour imported produce. Peri-urban milk suppliers may participate in value chains through wholesalers, but in remoter areas farms specialise in meat production, reliant on long chains of intermediaries. Only in Kazakhstan do international agreements, slaughter and animal health arrangements favour export prospects in the near future. Since the 1990s, winter fodder deficits have limited livestock productivity. Domestic fodder production is increasing in Kazakhstan and Kyrgyzstan, but is hindered by state order policies in Turkmenistan and Uzbekistan. Dairy producers close to markets often provide high quality fodder, whilst need for supplements is lower amongst mobile meat producers with winter pasture. Amongst the latter, a class of large commercial operations is emerging, whilst smaller farms lacking access to grazing resources find it harder to grow. Government policy often magnifies differences between small and large producers, for example through conditions for subsidies or land access procedures. Subsidised credit is available in most republics but uptake is limited by effective demand. Improved public services, better support for service cooperatives and decentralised processing and slaughter facilities would help producers increase value from their livestock.
urn:nbn:de:gbv:3:2-120441
Keywords: 330; Central Asia; livestock; marketing; fodder; pasture; policy